The Influence of Fiscal Policy on Regional Government Financial Performance: A Quantitative Analysis of Regional Budgets in Indonesia - M. Fadly Syahputra; Janitra Prabowo; Anto Andreawan (CV. Era Digital Nusantara, 2026)
This study is motivated by the importance of fiscal policy in improving the financial performance of local governments in the decentralization era. The purpose of this study is to analyze the effect of local own-source revenue, intergovernmental transfers, and regional expenditure on the financial performance of local governments in Indonesia. This research uses a quantitative approach with secondary data derived from local government financial reports and regional budgets for the period 2020 to 2024 obtained from official government institutions. The analytical method employed is panel data multiple linear regression using EViews software. The results show that local own-source revenue and regional expenditure have a positive and significant effect on financial performance, while intergovernmental transfers have a negative and significant effect. Simultaneously, all independent variables significantly influence financial performance. These findings indicate that optimizing integrated fiscal policies is essential to improve local government financial performance. This study concludes that strengthening fiscal independence and effective expenditure management are key factors in enhancing the quality of regional financial management.